EFEKTIFITAS KOMPRES KUBIS TERHADAP PEMBENGKAKAN PAYUDARA KARENA BENDUNGAN ASI - Yulisa, Alfia; Kamidah, Kamidah (Seroja Husada: Jurnal Kesehatan Masyarakat, 2024)
Background : Engorgement is the damming of milk caused by narrowing of the lactiferous ducts or glands that are not completely emptied. According to WHO 2020, mothers who experience engorgement are 66.87%. According to the Ministry of Health 2018, in Indonesia the incidence of postpartum women who experience engorgement is 5%. If engorgement are not treated immediately, it can cause mastitis which is caused by the bacterium Staphylococcus aureus. Handling engorgement dams can be done by breastfeeding as often as possible. If there are still engorgement dams, it can be handled using other anthropological methods, namely, local pus clots will occur in the breast, which is also called breast abscess. For the handling of engorgement, it can be done in a non-pharmacological way, which is compressing cabbage leaves and dadap serep (erythrina subumbrans) leaves. Objective: To determine the effectiveness of cabbage compresses against breast swelling due to engorgement. Method: This research uses the Quasi Experiment method with a Pretest Posttest With Control Group Design research design. The total sample was 20 respondents who were divided into 2 groups, namely 10 respondents as the intervention group were given cabbage compresses and 10 respondents as the control group were given Erythirna Subumbrans Merr compresses. Test analysis using MannWhitney. Results: Of the 10 respondents in the intervention group, 90% experienced recovery, while of the 10 respondents in the control group, 50% experienced recovery. The p value of 0,044 is smaller than 0,05 Conclusion: cabbage compress is effective in reducing breast swelling